Conservative management of displaced paediatric supracondylar fractures: a systematic review. (October 2018) - Yeomans, Daniel; Graham, Simon M; Mkandawire, Nyengo C; Harrison, William J; Perry, Daniel C
In low-income countries, where surgical expertise and resources are limited, displaced supracondylar fractures of the distal humerus are routinely managed with traction or closed reduction and casting. This is in contrast to high-income nations, where percutaneous K-wire fixation forms the mainstay of treatment. The aim of our study is to present the published evidence regarding the outcome of conservatively managed displaced supracondylar fractures in children. A systematic review of the literature was performed identifying 46 studies evaluating the outcome of displaced supracondylar fractures managed non-operatively. Our results show management by traction is equivalent to percutaneous pinning, whereas outcomes following closed reduction and casting were inconsistent. Traction therefore remains a viable option in low- and middle-income countries (LMICs). However, at present there are few data from LMICs, limiting the transferability of our conclusions.